2018
DOI: 10.1155/2018/4181626
|View full text |Cite
|
Sign up to set email alerts
|

Superposition Coded Modulation Based Faster‐Than‐Nyquist Signaling

Abstract: A structure of faster-than-Nyquist (FTN) signaling combined with superposition coded modulation (SCM) is considered. The socalled FTN-SCM structure is able to achieve the constrained capacity of FTN signaling and only requires a low detection complexity. By deriving a new observation model suitable for FTN-SCM, we offer the power allocation based on a proper detection method. Simulation results show that, at any given spectral efficiency, the bit error rate (BER) curve of FTN-SCM lies clearly outside the minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Moreover, NOMA transmission based on faster-than-Nyquist (FTN) signaling was also considered in the literature [12]. Indeed, FTN signaling is a classic nonorthogonal signaling scheme exhibiting an enhanced spectral efficiency [13]- [16], where data is transmitted at a symbol rate higher than the Nyquist intersymbol interference (ISI)-free rate 1 [19]. Although FTN-based NOMA (FTN-NOMA) transmission is expected to have an increased achievable rate, its theoretical rate analysis has not been disseminated in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NOMA transmission based on faster-than-Nyquist (FTN) signaling was also considered in the literature [12]. Indeed, FTN signaling is a classic nonorthogonal signaling scheme exhibiting an enhanced spectral efficiency [13]- [16], where data is transmitted at a symbol rate higher than the Nyquist intersymbol interference (ISI)-free rate 1 [19]. Although FTN-based NOMA (FTN-NOMA) transmission is expected to have an increased achievable rate, its theoretical rate analysis has not been disseminated in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…In his pioneering paper [1], Mazo showed that when signaling transmits 25% faster than Nyquist rate, the minimum Euclidean distance between binary phase shift keying (BPSK) modulated sinc pulses remains the same, which indicates that FTN signaling can boost the data rate by 25% without performance degradation or bandwidth expansion. More importantly, it has been proved that FTN signaling can achieve a higher Shannon capacity than classic Nyquist signaling with a non-sinc signaling pulse [2], [3]. Therefore FTN signaling has been recognized as bandwidth-efficient signaling scheme, which has a great potential for supporting high speed data transmissions in next generation wireless communication systems [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…e simulation results of Anderson et al [10] reveal that when the transmitted pulse has excessive bandwidth, FTN transmission can achieve higher capacity than transmission under Nyquist rate. In other works, the research of FTN has been extended on multicarrier systems [11,12] and low-complexity demodulation [13].…”
Section: Introductionmentioning
confidence: 99%